Using digital humanities in the classroom a practical introduction for teachers, lecturers and students - Battershill, Claire; Ross, Shawna (Bloomsbury Academic, 2017)
"The first practical guide to using digital tools and resources in the Humanities classroom."--Provided by publisher.